Immature stages of the genus Oxythyrea (Coleoptera: Scarabaeidae: Cetoniinae) with a key to third instar larvae, and notes on the biology of the genus - Vondráček, Dominik; Hadjiconstantis, Michael; Šípek, Petr (Zootaxa, 2018)
The genus Oxythyrea Mulsant, 1842 comprises ten currently recognized species. So far, larval descriptions for only three species are available. Here, we present comprehensive descriptions of third instar larval morphology for the six previously unstudied Oxythyrea species along with detailed re-descriptions of larval morphology for the previously described species. All descriptions are supplemented by photographs and line art drawings of the morphological structures. This work also contains a key to third instar larvae of the genus Oxythyrea as well as observations from collecting sites with focus on biological characteristics of all covered species including pictures of biotopes and host plants for adults. In addition, notes on the breeding circumstances for species are provided.